Effect of Blasting Treatments on the Surface Topography and Cell Adhesion on Biodegradable FeMn‐Based Stents Processed by Laser Powder Bed Fusion. Issue 10 (4th September 2022) - Paul, Birgit; Hofmann, Anja; Weinert, Sönke; Frank, Frieda; Wolff, Ulrike; Krautz, Maria; Edelmann, Jan; Gee, Michael W.; Reeps, Christian; Hufenbach, Julia
Abstract : Despite all progresses made so far, in‐stent restenosis (ISR) is still a vital problem after angioplasty and stenting with permanent stents. Therefore, the effects of microblasting on laser powder bed fusion (LPBF) manufactured biodegradable Fe‐based stents with regard to surface topography and its effect on smooth muscle cell (SMC) adherence, which could be interpreted as an early hallmark for ISR, are characterized. The LPBF‐processed Fe‐30Mn‐1C‐0.025S stents are microblasted with spherical glass beads and angular corundum particles. On the microscale, the partially molten particles on the stents are significantly reduced after the surface treatments, especially after microblasting with glass beads. Angular corundum particles lead to a rougher surface on the nanoscale as demonstrated by scanning electron microscopy and atomic force microscopy. With the aim to reduce migration and proliferation of SMC, which contribute to ISR after stenting, the interactions of microblasted stent surfaces with SMC are assessed by fluorescence microscopy. Both microblasted surfaces reduce SMC adhesion and change SMC morphology compared to the as‐built state as well as to commercially available 316L stents. In conclusion, microblasting treatment shows a high potential for the postprocessing of additively manufactured, biodegradable stents due to the reduction of the surface roughness and possible beneficial effect regarding ISR. Abstract : For biodegradable Fe‐based materials, as a new class of implant materials, surface treatments have to be developed. In this article, surface topography of filigree stent structures is mechanically modified by microblasting with spherical glass beads or angular corundum particles. The effect of different generated surface roughness on adhesion of primary smooth muscle cells is investigated.